(untitled) (Clinics, 2013)
OBJECTIVE: Frailty syndrome can be defined as a state of vulnerability to stressors resulting from a decrease in functional reserve across multiple systems and compromising an individual's capacity to maintain homeostasis. The purpose of this study was to determine the prevalence of frailty and its association with social and demographic factors, functional capacity, cognitive status and self-reported comorbidities in a sample of community-dwelling older individuals who are clients of a healthcare plan. METHODS: We evaluated 847 individuals aged 65 years or older who lived in the northern area of the city of Rio de Janeiro, Brazil. The subjects were selected by inverse random sampling and stratified by gender and age. To diagnose frailty, we used the scale proposed by the Cardiovascular Health Study, which consisted of the following items: low gait speed, grip strength reduction, feeling of exhaustion, low physical activity and weight loss. The data were collected between 2009 and 2010, and the frailty prevalence was calculated as the proportion of individuals who scored positive for three or more of the five items listed above. To verify the association between frailty and risk factors, we applied a logistic regression analysis. RESULTS: The prevalence of frailty syndrome was 9.1% (95% confidence interval [CI], 7.3-11.3); 43.6% (95% CI, 40.3-47) of the individuals were considered robust, and 47.3% (95% CI 43.8-50.8) were considered pre-frail (p